Whimseyshire - A Comedic Drama - Eichler, Hanna; von Randow, Hanna (Auckland University of Technology, 2014)
Whimseyshire is a contemporary comedic drama about family, the roles family members play, the masks they wear and the secrets that are held long after they should have been shared. Through the use of humour in the face of difficulty, it explores the concepts of how long held secrets have shaped the lives of three generations of women in the same family and their responses when the truth is revealed. Ultimately, the two younger women do come to understand the love they share and the love others have for them does not change when the nature of their relationship changes and this becomes the healing salve to their fresh and very tender wounds. Juxtaposed against this is the inability of other characters who are too entrenched in the lies and the keeping up of appearances to be able to accept that the truth has the ability to create personal freedom.
Keywords: Comedy; Drama; Screenplay